Teratogenic effects of amniotic sac puncture: a mouse model - MacIntyre, D J; Chang, H H; Kaufman, M H (Journal of anatomy, 1995)
The possibility of an association between chorionic villus sampling (cvs) and limb abnormalities has prompted a review of the relevant experimental data. Although a vascular aetiology is favoured by many at present, the possibility exists that a proportion of cases may be caused by oligohydramnios secondary to inadvertent amniotic sac puncture. A mouse model of amniotic puncture syndrome has been developed to study the craniofacial and limb abnormalities produced by this procedure. Pregnant mice were anaesthetised and a laparotomy performed. One uterine horn was exteriorised, and the amniotic sacs punctured through the wall of the uterus with either a 21 gauge or a 25 gauge needle. The conceptuses in the contralateral uterine horn acted as controls. The mice were all killed on d 19 of pregnancy (day of finding a vaginal plug = d 1 of pregnancy) by cervical dislocation, and the morphological features of the embryos examined in detail. In a preliminary study, amniotic sac puncture was carried out on d 12, 13, 14, 15 or 16 of pregnancy, with either a 21 or a 25 gauge needle. Since the highest rates of palatal defects and limb deformities were observed following amniotic sac puncture using a 21 gauge needle, when this procedure was carried out on either d 13 or 14 of pregnancy, the main study was undertaken using a 21 gauge needle on these two days of pregnancy. Of 102 embryos in which amniotic sac puncture was carried out on d 13, 53% survived to d 19. Of the latter, 35% had a cleft palate, 61% had one or more morphologically abnormal limbs, and 43% had an abnormal tail. When amniotic sac puncture was carried out on d 14 of pregnancy, of 83 embryos subjected to this procedure, 81% survived to d 19. Of the latter, 27% had a cleft palate, 39% had one or more morphologically abnormal limbs, and 19% had an abnormal tail. In the controls, of 86 and 61 embryos isolated respectively from the d 13 and 14 mice, the survival rates were 97 and 90%, respectively. Palatal, limb and tail abnormalities were not observed in the control series. Tentative relationships are drawn between cvs and amniocentesis-associated abnormalities, the Robin sequence and their rodent phenocopies.